The utility of CXCL13 and circulating CXCR5+ T cell detection in the diagnosis of systemic lupus erythematosus associated nephritis - Liu, Yu; Tan, Si-Yu; Huang, Meng-Ke; Yang, Yun-Long; Hui, Lu; Liu, Ting (Frontiers in Immunology, 2025)
IntroductionCXCL13 regulates the homing of lymphocytes. It is highly expressed in kidney and serum of SLE patients, and correlates with disease activity, but its value in LN is unclear. This study was to investigate the expression and diagnostic value of CXCL13 and its regulated CXCR5+ T cells in LN.MethodsIn mice, the association of serum CXCL13 levels with renal function was analyzed. And CXCR5+ T cell was detected by H&E staining and immunofluorescence in kidney, and by flow cytometry in spleen. In clinical studies, the association of CXCL13 and CXCR5+ T cells with disease activity was verified, and their diagnostic efficacy was assessed by ROC curves.ResultsCXCL13 was elevated in both mouse and patients, and was positively correlated with disease severity. Serum CXCL13 had an AUC of 0.9287 in the diagnosis of SLE and 0.6244 in differential diagnosis of LN. And in MRL/lpr mice, CXCL13 was involved in the development of nephritis by promoting the recruitment of CXCR5+ T cells to the kidney. In the peripheral blood of LN patients, CXCR5+ T cells were significantly reduced. Combined detection of CXCR5+ T cell subsets resulted in an AUC of 0.9672 for the diagnosis of SLE and 0.7867 for the differential diagnosis of LN.DiscussionSerum CXCL13 has high accuracy in the diagnosis of SLE, and circulating CXCR5+ T cells may serve as a novel biomarker for the diagnosis of SLE and LN, which might complement the poor performance of serum CXCL13 in the diagnostic efficacy of LN.